Prevalence of high aldosterone-renin ratio and plasma aldosterone levels among hypertensive patients at a primary care clinic - Omar , Ahmad Marzuki; Abd Rahim, Firdaus; Sukor, Norlela; Shahar, Mohammad Arif; Kamaruddin, Nor Azmi (Malaysian Endocrine and Metabolic Society, 2013)
Screening test by using aldosterone-renin ratio (ARR) resulted in a higher prevalence (5-15%) of primary aldosteronism than was previously expected but to date there is no such study performed in Malaysia. Objectives: The aim of the study was to determine the prevalence of high ARR (>20) and high plasma aldosterone concentration (PAC) (>150 pg/mL) in hypertensive subjects attending a primary care clinic. Methods: This was a cross-sectional study involving 220 essential hypertension subjects from a primary care clinic in Kuala Lumpur. Bloods for aldosterone, renin and renal profile were taken as specified in previously published protocols. Results: The prevalence of positive test for PA was 7.3%. When either ARR>20 or PAC >150 pg/mL were used, 15.0% and 17.7% of subjects fulfilled the criteria, respectively. Conclusions: The prevalence of hypertensive subjects with high ARR (>20) and PAC (>150 pg/mL) was 7.3%, justifying the need to investigate this group of subjects for PA.